2014
DOI: 10.3988/jcn.2014.10.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems Associated with Behavioral and Psychological Symptoms as Well as Cognitive Functions in Alzheimer's Disease

Abstract: Background and PurposeIt has been shown that sleep problems in Alzheimer's disease (AD) are associated with cognitive impairment and behavioral problems. In fact, most of studies have founded that daytime sleepiness is significantly correlated with cognitive decline in AD. However, a few studies have also shown that nighttime sleep problems are associated with cognitive function and behavioral symptoms in AD. Accordingly, the aim of this study was to evaluate the effects of nighttime sleep on cognition and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 27 publications
4
47
0
Order By: Relevance
“…Sleep disorders or nocturnal behavioral disturbances predispose to earlier nursing home placement [33,34], are associated with poorer functional status [35], and worsened cognitive function [36], and may predict earlier mortality [37].…”
Section: Alzheimer's Disease Which Sleep Disturbances Are Common In Pmentioning
confidence: 99%
“…Sleep disorders or nocturnal behavioral disturbances predispose to earlier nursing home placement [33,34], are associated with poorer functional status [35], and worsened cognitive function [36], and may predict earlier mortality [37].…”
Section: Alzheimer's Disease Which Sleep Disturbances Are Common In Pmentioning
confidence: 99%
“…There have been suggestions that a possible bidirectional relationship exists between alterations in sleep rhythm and the development of dementias {particularly Alzheimer disease (AD)} ( Ju et al, 2014;Guarnieri and Sorbi, 2015;Villa et al, 2015;Urrestarazu and Iriarte, 2016). This is based on the facts that; a) changes in sleep have been observed to predate the onset of cognitive symptoms in patients with dementia (AD), with a decline in sleep quality and/or circadian function occurring in parallel with both cognitive dysfunction and the progression of disease (see Ju et al, 2014 for review) .b) sleep disturbances and disruption of the neural regulation of the sleep-wake rhythm appear to be involved in the cellular and molecular mechanisms of cognitive decline (Guarnieri and Sorbi, 2015), and have been associated with severity of memory and cognitive impairment (Shin et al, 2014), c) alteration in sleep rhythm has a significant impact on physical, physiologic and cognitive functioning in individuals with dementias and are positively associated with the severity of behavioural dysfunction and cognitive impairment (Guarnieri and Sorbi, 2015). Studies have also reported that the concentrations of amyloid-β (Aβ) have a diurnal variation, with levels rising during wakefulness and the nadir during sleep (Huang et al, 2012;Lucey and Bateman, 2014); there are also reports that sleep facilitates Aβ clearance, a function which may be impaired with sleep disturbance ( Ju et al, 2014;Miller, 2015).…”
Section: Role Of Sleep In Cognition and Neurocognitive Declinementioning
confidence: 99%
“…Sleep problems are very common in Alzheimer' s disease and other dementias (Shin et al, 2014). Pharmacological treatment for insomnia and other sleep disturbances in dementia depends upon the underlying cause.…”
Section: Pharmacotherapy For Insomniamentioning
confidence: 99%